PRINCIPLES OF PELVIC FRACTURE TREATMENT IN POLYTRAUMA PATIENTS - Dabetic, Uros; Golubović, Danilo; Grupkovic, Jovana; Ilić, Marko; Aleksandrić, Dejan; Tulić, Goran (Srpski medicinski časopis Lekarske komore, 2022)
Introduction: The treatment of pelvic fractures is one of the biggest challenges in orthopedic surgery and traumatology. Mortality from these injuries can be as high as 21%, which is why recognizing them and providing adequate treatment is of great importance. The most common cause of death in the first 24 hours following injury is bleeding. Pelvic fractures range from simple to complex fractures with consequent hemodynamic instability. The aim of this study is to assess current standards of pelvic fracture care, as well as to indicate a possible strategy to improve the final outcome of treatment. Results: When there is no established protocol, the on-duty team of doctors is guided by the guidelines available to them. More recently, DCR has been considered a guiding principle in the care of polytraumatized patients. It is of primary importance to establish bleeding control – using PPP, angiographic embolization or the REBOA method. The use of pelvic bandages is recommended in literature as the primary form of care for pelvic injuries by the emergency service or by a trained person in pre-hospital conditions. External fixation of unstable pelvic fractures is one of the key steps in the DCR protocol. ORIF of pelvic fracture is a definite type of fracture fixation, but it is performed only in hemodynamically stable patients. Conclusion: Due to the anatomical characteristics of the pelvic cavity, pelvic ring injuries represent only a part of the spectrum of polytrauma, therefore the treatment is initially based on the hemodynamic stabilization of the patient (DCR protocol). The treatment of such patients requires a multidisciplinary approach. Placement of an external fixator as part of the DCO protocol has a role in bleeding control and is the method of choice in hemodynamically unstable patients. Definitive pelvic fracture fixation (ORIF) is performed in hemodynamically stable patients, who are not in life-threatening condition.